THE INFLUENCE OF READING INTEREST ON GPA OF STUDENT OF BUILDING ENGINEERING EDUCATION OF PALANGKARAYA UNIVERSITY IN EVEN SEMESTER ACADEMIC YEAR 2012/2013 - Whendy Trissan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
“No day without reading ". The sentence was clearly no stranger into a creed (beliefs, convictions) which thronged various enlightenment room in our country. Unfortunately, our nation does have a sense of ignorance that was so severe. Thousands of creed, slogans, mottos lined up, all just be on display. However, reading is a necessity. By reading one can obtain the information needed, stimulates creativity, encourages the emergence of a desire to be able to think critically and systematically, expand, and enrich the knowledge and form a winning personality and competitive. Insightful society is easy to be proactive to the times. Not only important, but also urgent due to read something is the key to build civilization. The behaviours of the students of Building Technical Education FKIP Universitas Palangka Raya in reading are different, there are as lectures took place, there were reading when at home, or anyone reading through the discussion, but this activity is rare to be done. Most of the students choose chatted with his/her friends while waiting Lecturer or to be elsewhere more than reading the books they brought. Therefore, the researchers intend to find out the influence of students' reading interest to their GPA for one encountered semester. Not many students brought relevant books to their class. Only a few students carry the book relevant to the subjects that followed, while others are usually only carry binders or writing books. The result of the research shows that there is a relationship (correlation) between the interest in reading and the students’ GPA.